Analisis Strategi Pemanfaatan Media Komunikasi KPU Kota Makassar dalam Meningkatkan Partisipasi pemilih pada Pilkada Serentak tahun 2020 - Kasim, Sri; Febri Sonni, Alem; Farid, Muhammad (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
The simultaneous regional head elections in 2020 will be the first regional elections to be held during the Covid-19 pandemic. The rules and policies set by the government in tackling the spread of Covid-19 are the biggest challenge for the General Elections Commission as the organizer of the regional election in dealing with the issue of low public interest in attending and exercising their right to vote at polling stations. In increasing voter participation, the Makassar City KPU, which is also the organizer of the regional election, faces this challenge by using a strategy through the use of communication media. Communication media has been widely used to support the implementation of socialization in increasing voter participation in regional head elections. This study aims to analyze the strategy used by the Makassar City KPU in utilizing communication media to increase voter participation in the 2020 Simultaneous Regional Head Elections held during the Covid-19 Pandemic. The method used in this study is a qualitative descriptive method with data collection carried out by observation, interviews and documentation studies. This research conducted The informant selection technique used purposive sampling. The results of this study found that the strategy carried out through the use of communication media by the Makassar City KPU could maximize the implementation of the socialization stages during the pandemic through various forms of social media so as to boost voter interest to participate in the 2020 simultaneous elections.